2002
DOI: 10.1021/jp0203550
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on the Rearrangement between the Isomers of C60X (X = O and S)

Abstract: The rearrangements between the closed [6,6] and open [5,6] isomers of C60O, as well as the closed [6,6], closed [5,6], and open [5,6] isomers of C60S have been studied using semiempirical AM1 and MNDO methods. The results show that the interconversion of the two isomers of C60O follows a two-step pathway involving an intermediate and two transition states. The calculated activation barriers for the migration of oxygen from [6,6]-bond to [5,6]-bond through an intermediate are 189.1 and 54.6 kJ mol-1, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
70
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(78 citation statements)
references
References 35 publications
5
70
3
Order By: Relevance
“…It can be seen from Table 2 that as the number of O atom increases, the binding energies of the fullerene oxides become more negative. Meanwhile, our results agree with those of previous works [17,20] that [5,6] C 60 O is more stable than [6,6] C 60 O from the total energy and binding energy. C 60 O had represented a longstanding case of experiment-theory disagreement, and there has been a similar problem with C 60 O 2 .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…It can be seen from Table 2 that as the number of O atom increases, the binding energies of the fullerene oxides become more negative. Meanwhile, our results agree with those of previous works [17,20] that [5,6] C 60 O is more stable than [6,6] C 60 O from the total energy and binding energy. C 60 O had represented a longstanding case of experiment-theory disagreement, and there has been a similar problem with C 60 O 2 .…”
Section: Resultssupporting
confidence: 93%
“…The optimized structures were confirmed as the local minima by frequency analyses at the HF/ STO-3G level of theory, and the lowest frequencies are 224. [20,21] were the most stable. As was displayed in Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It will be interesting to see, in future computational work, if the activation energy for either isomerization is significantly different than the DFT-predicted 175 kJ mol -1 activation energy for the isomerization of 6/6 epoxide-C 60 O to 5/6 ether-C 60 O. 69 Interestingly, we also found that many ether isomers of a different kind are up to 52 kJ mol -1 more stable than the most stable isomer shown in Figure 9. These are the trifluoromethoxytris(trifluoromethyl) isomers, C 60 (OCF 3 )(CF 3 ) 3 , and the relative ∆H f°v alues for 10 of them are listed in Table S-1. Since the OCF 3 group has an additional torsional degree of freedom compared to the CF 3 group, several isomers with o-C 6 -(OCF 3 )(CF 3 ) hexagons were among the most stable.…”
mentioning
confidence: 96%
“…Our results indicate that it is critical to optimize the temporal overlapping of the constituent solitons of an SC in order to impulsively excite molecular vibrational modes over a broader frequency range, which can lead to an increased measurement range of CARS. In addition, by applying the XFROG algorithm, which is a well-known technique for characterizing ultrashort pulses [10] and has been previously applied to CARS, [11,12] we have retrieved the molecular optical response function under SC impulsive excitation from a series of time-resolved CARS spectra, or CARS spectrogram, and obtained a digital CARS spectrum with spectral resolution significantly better than the bandwidth of the probe pulses. Background-free CARS can be realized by digitally truncating the initial part of the CARS spectrogram, which contains the nonresonant electronic contribution.…”
Section: Introductionmentioning
confidence: 99%